1979
DOI: 10.1038/bjc.1979.287
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A, zinc and lung cancer

Abstract: Summary.-Serum vitamin A concentrations were measured in 26 newly diagnosed lung -cancer patients and found to be significantlv lower than those of patients of similar age with either non-malignant lung or non-lung diseases. The levels of vitamin A in the lung-cancer patients, but not in the controls, were significantly correlated with serum concentrations of retinol-binding protein (RBP) and zinc. It is suggested that low levels of zinc might reduce the synthesis of RBP and thus reduce the mobilization of vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 23 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…Our findings agree with those of previous retrospective studies (13)(14)(15), and except for one study (16). further support for our data is provided by prospective epidemiological studies (8,(17)(18)(19) retrospective studies (20).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings agree with those of previous retrospective studies (13)(14)(15), and except for one study (16). further support for our data is provided by prospective epidemiological studies (8,(17)(18)(19) retrospective studies (20).…”
Section: Discussionsupporting
confidence: 93%
“…Low plasma levels of vitamin A have also been found in patients with lung cancer and this has been confirmed in a larger series of patients (Atukorala et al 1979). In this latter at https://www.cambridge.org/core/terms.…”
supporting
confidence: 58%
“…However, in a case-control study, the plasma concentrations of RBP were found to be normal in samples taken 2-7 years before the development of clinically manifested lung tumours (Haines et al, 1982). While there have been a number of studies showing low concentrations of both plasma retinol and RBP in patients with an established tumour (Atukorala et al, 1979;Basu et al, 1982).…”
Section: Discussionmentioning
confidence: 93%
“…Subnormal levels of plasma retinol have been reported in cancers of the bronchus (Basu et al, 1976); lung (Atukorala et al, 1979); oropharynx (Ibrahim et al, 1977) and GI tract (Abels et al, 1941). In these studies, blood samples were taken from patients who still had a tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation